MOTIVATION OF STUDYING WITH THE HELP OF INFORMATION SYSTEMS - Fedorovich, Ivanko Alexander; Alexandrovich, Ivanko Mikhail; Kulikova, V.; Yu., Sultanova (International Journal of Research -GRANTHAALAYAH, 2018)
Information technology is widely used in the educational process. To increase the motivation for learning, various methodical methods and means are used. The experience of using the "matrix" information system shows how interest appears to the learning process and all its participants: teachers and students. The article is of interest to all participants of the educational process.